The Deixis used by Billie Eilish - Donkaewbua, Sangrawee (Chophayom Journal, 2025)
The word “deixis” is a technical word that is not commonly heard and understood. However, it is the foundational base of all communication. That is because one of the most basic form of communication a human makes is by pointing. Deictic expressions are sometimes called “indexical” meaning that the expression is a form of referring. This article will be examining the deixis used by Billie Eilish, the IT girl of now from the music industry. She is known for being success in the business in her youth, talking and singing in different style and tune. Through quantitative data analysis, this study has demonstrated how all three of her interviews used language, especially deixis to communicate her visions in such a way that her music work and motivation in doing the work have inspired millions across the globe. In all the three interviews Billie Eilish gave, the highest frequency is person deixis, followed by discourse deixis, space deixis, temporal deixis and social deixis.